Project management and presentation of information in financial statements - company performance measurement or project performance measurement - Kalinowski, Jacek (Comparative Economic Research. Central and Eastern Europe, 2010)
Realization of projects is such form of operation which in the recent years – in the age of globalization of economy and growing competition – has become more and more significant, both in Poland and worldwide. The value and the number of projects realized are gradually growing and include not only the branches traditionally related to such form of operation (e.g. construction and IT industry) but in practice all fields of our life. A necessary element that determines the success of project realization is timely information which also needs to be reliable and useful. The source of such information is the accounting system composed of two subsystems: financial accounting (focused on the external recipient of the information) and management accounting (providing information to internal recipients). One of the basic determinants of creating information for external recipients (such as investors, banks, insurance companies, treasury administration organs etc.) is comparability. Keeping it influences the quality of information regarding project activity taken from financial reports created according to the selected regulations of accounting (e.g. IAS/IFRS, US GAAP and the PL GAAP). The aim of the article is to draw the attention to the problems related to the presentation of the operational result in case of companies realizing projects contained in a financial report. The article is of discursive nature since the issues that it deals with usually depend on what given solution is selected bya unit in question. Moreover, some of the areas are subject to detailed regulations of the balance law (both domestically – the Act on Accounting and PL GAAP No. 3, and internationally – AS/IFRS). However, their applicationmay lead to ‘blurring’ a realistic and true picture of the capital and financial situation of a company realizing long-term projects.